Adapting to climate change under threats of violence: A comparative institutional analysis of incentives for conflict and collaboration - Medina, Leonardo; Pacillo, Grazia; Laderach, Peter; Sieber, Stefan; Bonatti, Michelle (Elsevier, 2025)
Research on climate and conflict often emphasizes violence and its drivers, overlooking the prevalence of collaboration in shaping social relations. Addressing this gap, this study undertakes a comparative institutional analysis of community-level responses to climate threats in violence-prone settings. The research explores conditions that incentivize either cooperation or conflict, refraining from presuming one outcome as dominant. Using a structured analytical framework applied through a thematic analysis, it systematically examines environmental, relational, institutional, and systemic patterns across three case studies of localized collective adaptation to climate change under varying forms of violence. These case studies are located in Guatemala, Philippines and Kenya. The study identifies 18 factors that drive conflict or foster collaboration, revealing that while these factors are broadly consistent across contexts, their effects are highly context-dependent. In some cases, the same factor contributes to both conflict and collaboration within shared adaptation arenas, underscoring the complex interplay of drivers. These findings highlight the importance of analysing interactions among drivers when designing collective climate adaptation efforts, emphasizing opportunities to mitigate violence and foster collaboration. The study concludes that enhancing adaptive capacities and climate-resilient peace requires expanding adaptation strategies to address often-overlooked dynamics. These include the historical processes underpinning institutional multiplicity, the legitimacy of local security forces, and the cohesion among neighbouring communities. By realigning incentives toward collaboration, such interventions can simultaneously build resilience and advance peaceful relations, providing actionable insights for policymakers and practitioners working in violence-prone regions.